(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article examines the current state of insurance activity and trends in development based on competition. Several problems of competition between insurance companies in the insurance market have been analyzed and a number of solutions have been proposed.